Environmental Knowledge, Race, and African American Literature - Klestil, Matthias (Springer Nature, 2023)
This open access book suggests new ways of reading nineteenth-century African American literature environmentally. Combining insights from ecocriticism, African American studies, and Foucauldian theory, Matthias Klestil examines forms of environmental knowledge in African American writing ranging from antebellum slave narratives and pamphlets to Charlotte Forten’s journals, Booker T. Washington’s autobiographies, and Charles W. Chesnutt’s short fiction. The volume highlights how literary forms of environmental knowledge in the African American tradition were shaped by the histories of slavery and race, mainstream environmental writing traditions, and African American forms of expression and intertextuality. Turning to the Underground Railroad, debates over education and home-building, and the aesthetics of the pastoral and the georgic, Environmental Knowledge, Race, and African American Literature provides an original perspective on the African American ecoliterary tradition that uncovers new facets of canonical and understudied texts and offers new directions for ecocriticism and African American studies.